Pengaruh Media Pembelajaran Lumio By Smart Terhadap Hasil Belajar Kognitif Peserta Didik pada Mata Pelajaran Pendidikan Pancasila dan Kewarganegaraan - Rasiana, Rara; Yuni Lestari, Ria; Alwan Bahrudin, Febrian (Faculty of teaching training and education, 2025)
This study aims to examine the impact of using Lumio by SMART as a learning medium on students' cognitive learning outcomes in the subject of Pancasila and Civic Education. A quantitative approach was employed, utilizing a quasi-experimental design, specifically the pre-test post-test only control group model. The sample consisted of 78 students, selected through purposive sampling, and divided into two groups: class VIII-1, serving as control group, received instruction with PowerPoint as a teaching aid, and class VIII-5, designated as experimental group, received instruction using Lumio by SMART as the learning medium. The main instrument used in data collection was a cognitive learning outcome tests, which was complemented with documentation of various supplementary data sources. Data analysis was conducted using an independent sample t-test, which showed a significant value of 0.000 (0.000 ≤ 0.05). These results indicated that there was a positive and significant effect from using of Lumio media by SMART on the improvement of students’ learning outcome, thus (H1) is accepted, and (H0) is rejected.